2017
DOI: 10.1016/j.concog.2017.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Mind-wandering and task stimuli: Stimulus-dependent thoughts influence performance on memory tasks and are more often past- versus future-oriented

Abstract: Although many studies have indicated that participants frequently mind-wander during experimental tasks, relatively little research has examined the extent to which such thoughts are triggered by task stimuli (stimulus-dependent thoughts; SDTs) versus internally triggered (stimulus-independent thoughts; SITs). In the current experiment, we assessed differences in the frequency and characteristics of SDTs and SITs, as well as their associations with subsequent memory in young adults. Whereas frequency of SDTs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 49 publications
3
38
0
Order By: Relevance
“…In relation to mind-wandering, Berntsen puts forward the view that research conducted on future-oriented mindwandering may not be tapping into spontaneous episodic future thinking because of a number of methodological and conceptual issues in terms of how mind-wandering has been defined and studied so far, and recent findings showing that a substantial amount of mind-wandering episodes are initiated intentionally. While we share Berntsen's concerns, there is ample evidence that the field of mind-wandering has entered into a new phase by introducing the distinctions between intentional vs. unintentional (e.g., Seli, Risko, Smilek, & Schacter, 2016) and stimulus-dependent vs. stimulus-independent mind-wandering (e.g., Maillet, Seli, & Schacter, 2017). With these distinctions and improved methodologies tapping into the precise content of thoughts (e.g., Irish et al, 2019;Warden et al, 2019), we believe that research on future-oriented mind-wandering and spontaneous episodic future thinking will have much in common in terms of conceptual understanding and experimental findings.…”
Section: The Present: Major Themes and Content Of The Special Issuementioning
confidence: 85%
“…In relation to mind-wandering, Berntsen puts forward the view that research conducted on future-oriented mindwandering may not be tapping into spontaneous episodic future thinking because of a number of methodological and conceptual issues in terms of how mind-wandering has been defined and studied so far, and recent findings showing that a substantial amount of mind-wandering episodes are initiated intentionally. While we share Berntsen's concerns, there is ample evidence that the field of mind-wandering has entered into a new phase by introducing the distinctions between intentional vs. unintentional (e.g., Seli, Risko, Smilek, & Schacter, 2016) and stimulus-dependent vs. stimulus-independent mind-wandering (e.g., Maillet, Seli, & Schacter, 2017). With these distinctions and improved methodologies tapping into the precise content of thoughts (e.g., Irish et al, 2019;Warden et al, 2019), we believe that research on future-oriented mind-wandering and spontaneous episodic future thinking will have much in common in terms of conceptual understanding and experimental findings.…”
Section: The Present: Major Themes and Content Of The Special Issuementioning
confidence: 85%
“…Several recent studies have shown that MW is a cue-dependent phenomenon, triggered by both internal and external events. Specifically, there is evidence that both task-irrelevant and task-relevant external stimuli [7][8][9][10][11]13] might act as triggers for MW episodes. In a recent study, Pelagatti et al [21] found a significantly larger pupil dilation following cue-words reported by participants as the trigger of MW compared to non-trigger words (with similar emotional content), and the pupil dilation appeared to increase over time.…”
Section: Discussionmentioning
confidence: 99%
“…According to Klinger's current concerns hypothesis [4,5,6] "spontaneous thoughts are probably triggered by cues (meaningful stimuli) that may be external in the environment or internal in the person's own mental activity and that are associated with one or another of the individual's goals" [6, p. 216]. Over the last years, an increasing number of studies [7][8][9][10][11][12][13] have investigated the potential contribution of environmental stimuli (not only goal-related stimuli) to MW. The results converge in showing that both task-relevant [7][8][9] and task-irrelevant external stimuli [10,11,13] Running head: Timecourse of mind wandering 4 might indeed act as triggers for MW, challenging the traditional view of MW as completely stimulus-independent [14] and self-generated mental activity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the findings appear to indicate that "environmental stimuli regularly trigger mind-wandering episodes" (p.56, Maillet et al, 2017), which calls for some reconceptualization of mind-wandering as purely stimulus-independent (cf. .…”
Section: Cdr-based Classification Used By Gyurkovics Et Al (2017) Amentioning
confidence: 94%
“…In addition, as pointed out by Maillet et al (2017), the cues may or may not be present at the time when the thought comes to mind. …”
Section: Footnotesmentioning
confidence: 99%